Kekudusan Yang Transformatif: Aktualisasi Teladan Maria Dalam Pembentukan Iman Dan Moral Perempuan Kristiani Masa Kini - Undat, Rikardus; Senda, Siprianus Soleman; Subani, Yohanes; Silab, Theodorus (Pastoralia Jurnal Penelitian Dosen, 2025)
This article examines the example of the holiness of Mary, the mother of Jesus, as a paradigm in the formation of the faith and morals of contemporary Christian women. The background of this study departs from the reality of the decline in moral and spiritual values ​​experienced by many Christian women amidst the currents of modernity, secularism, and the crisis of religious identity. This phenomenon is reflected in the weakening of faith commitment, a decline in moral integrity, and a shift in life orientation from spiritual values ​​to material and individualistic interests. In this context, the discussion focuses on how the example of Mary's holiness can be implemented concretely in the formation of the faith and morals of contemporary women, namely through obedience to God's will, faithfulness in prayer, and the experience of love in social relationships and daily life responsibilities. The main objective of this study is to explore and actualize the values ​​of Marian holiness, such as obedience, humility, purity, and loyalty so that they can become a concrete inspiration for Christian women in living a life based on faith. The method used in this study is a qualitative approach with theological-biblical analysis and literature study of various sources of Scripture and Church documents. The results of this study illustrate that Marian spirituality has transformative value in shaping the character of Christian women who are spiritually strong and morally upright. In conclusion, Mary's exemplary life is not only historical and symbolic, but also actual and contextual, serving as a life paradigm for Christian women in facing the challenges of faith and ethics in the modern era.